Increased frequencies of CD4(+) CD25(high) regulatory T cells in acute dengue infection - Simmons, Cameron (2018)
Dengue virus infection is an increasingly important tropical disease, causing 100 million cases each year. Symptoms range from mild febrile illness to severe hemorrhagic fever. The pathogenesis is incompletely understood, but immunopathology is thought to play a part, with antibody-dependent enhancement and massive immune activation of T cells and monocytes/macrophages leading to a disproportionate production of proinflammatory cytokines. We sought to investigate whether a defective population of regulatory T cells (T reg cells) could be contributing to immunopathology in severe dengue disease. CD4(+)CD25(high)FoxP3(+) T reg cells of patients with acute dengue infection of different severities showed a conventional phenotype. Unexpectedly, their capacity to suppress T cell proliferation and to secrete interleukin-10 was not altered. Moreover, T reg cells suppressed the production of vasoactive cytokines after dengue-specific stimulation. Furthermore, T reg cell frequencies and also T reg cell/effector T cell ratios were increased in patients with acute infection. A strong indication that a relative rise of T reg cell/effector T cell ratios is beneficial for disease outcome comes from patients with mild disease in which this ratio is significantly increased (P < 0.0001) in contrast to severe cases (P = 0.2145). We conclude that although T reg cells expand and function normally in acute dengue infection, their relative frequencies are insufficient to control the immunopathology of severe disease.